Sharing intention of electronic health records in online health communities: Patients’ behavioral decisions in the context of privacy protection measures - Shanshan Guo; Yuanyuan Dang; Bofei She; Yugang Li (Frontiers in Psychology, 2022)
Online health communities (OHCs) have become more important to people’s daily lives on the foundation of the voluntary sharing of electronic health records (EHRs). However, no in-depth investigation has been conducted concerning the influence of the perceptions of privacy protection among patients on their willingness to share EHRs. To fill the knowledge gap, by combining and modifying the theory of planned behavior (TPB) and the health belief model in the context of the privacy protection models implemented by OHCs, an empirical research method using a questionnaire approach is conducted to validate the hypotheses. The results indicate that the more positive a patient’s attitude toward medical information sharing behavior is, the higher that patient’s level of perceived behavioral control; in addition, the greater the social rewards obtained from this process, the more willing the patient is to share his or her EHRs after privacy protection measures are implemented by OHCs. Meanwhile, the effects of past positive experiences and disease severity have also been tested. The findings of this study can be used to promote patients’ full participation in OHCs from a privacy perspective and offer theoretical and practical suggestions to promote the development of OHCs.